Remote Education in Mexico: Advantages and Disadvantages - Gabriela Palavicini; Adriana Cantón (SAGE Open)
Technology has been an indispensable tool for education following the COVID-19 pandemic. Some habits adopted during that period, such as remote learning and teaching, have not yet been wholly abandoned, even if they occur in a minor measure since they can improve learning by adopting technology and developing technological skills. The research question is: How does technology influence the improvement of remote learning? The main objective is to provide information about the influence of technological advances on education, allowing people to become “smarter” according to Transhumanist theory, despite the results of learning losses, during the pandemic. To answer the main question, we considered the Mexican case during the pandemic, and a perspective for future years will be presented by re-examining those teaching practices related to the learning acquired using technological tools during that period. Following a mixed approach, we conducted a literature review analyzing and triangulating documental and theoretical works. Furthermore, we undertook a quantitative analysis to study the possible relationship between technological advances, learning losses, and the human condition with remote learning during the pandemic. The results proposed mostly a negative relationship amongst the variables considered, as students preferred face-to-face learning over remote education.